2019
DOI: 10.1073/pnas.1907660116
|View full text |Cite
|
Sign up to set email alerts
|

Immune effector monocyte–neutrophil cooperation induced by the primary tumor prevents metastatic progression of breast cancer

Abstract: Metastatic behavior varies significantly among breast cancers. Mechanisms explaining why the majority of breast cancer patients never develop metastatic outgrowth are largely lacking but could underlie the development of novel immunotherapeutic target molecules. Here we show interplay between nonmetastatic primary breast cancer and innate immune response, acting together to control metastatic progression. The primary tumor systemically recruits IFNγ-producing immune effector monocytes to the lung. IFNγ up-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 53 publications
1
45
3
Order By: Relevance
“…In apparent contrast with the previous findings, neutrophils recruitment and activation in the metastatic niche was found to be important for the reduction of metastasis formation through the killing of cancer cells [ 162 , 163 ]. Genetic ablation of the atypical chemokine receptor 2 (ACKR2) resulted in increased levels of chemokine receptors (i.e.…”
Section: The Role Of Neutrophils In Cancercontrasting
confidence: 82%
See 1 more Smart Citation
“…In apparent contrast with the previous findings, neutrophils recruitment and activation in the metastatic niche was found to be important for the reduction of metastasis formation through the killing of cancer cells [ 162 , 163 ]. Genetic ablation of the atypical chemokine receptor 2 (ACKR2) resulted in increased levels of chemokine receptors (i.e.…”
Section: The Role Of Neutrophils In Cancercontrasting
confidence: 82%
“…A recent study has demonstrated a mechanism that may explain, at least in part, why breast cancer patients develop metastasis [ 162 ]. The injection of human breast cancer cells with low spontaneous metastatic potential in non-obese diabetic (NOD)/severe combined immunodeficient (SCID) mice, resulted in reprogramming of neutrophils in the pre-metastatic lung.…”
Section: The Role Of Neutrophils In Cancermentioning
confidence: 99%
“…Non-metastatic cancer cells can mobilize IFNγ-producing monocytes to the lungs. IFNγ release activates TMEM173/STING within neutrophils, which stimulates neutrophil-mediated killing of disseminated cancer cells in the lungs ( 24 ).…”
Section: Anti-tumor Neutrophil Functionsmentioning
confidence: 99%
“…In addition, the microenvironment in the (pre)metastatic organ may induce dormancy 11 by different signals such as an endothelial cell-derived thrombospondin-1 12 or TGF-β2 produced in the bone marrow 13 . Only few studies addressed the influence of cancer cell-extrinsic factors such as innate 14,15 and adaptive immunity 16,17 on dormancy. Although infiltration of the primary tumor by T cells was shown to correlate with a good prognosis 18 , it 5 remains unclear whether this correlation is explained by cytotoxic T cells that eliminate cancer cells or by T cells that prevent the outgrowth of cancer cells and induce dormancy 19,20 .…”
Section: Introductionmentioning
confidence: 99%